Sonderkommando Dora – Special Military Geoscientific Unit of the German Counter-Intelligence Sevice in North Africa 1942 - Häusler, Hermann (Scientia Militaria - South African Journal of Military Studies, 2018)
The counter-intelligence service of the German Armed Forces High Command launched Operation Dora in 1941 to update terrain information of North Africa for the German warfare and to reconnoitre the frontier between Libya and Chad. This article presents Sonderkommando Dora as an example of military geoscientific reconnaissance during World War II in the North African theatre of war where the German Armed Forces needed more accurate military geographic information on the Western Desert, The scientific personnel comprised geographers, cartographers, geologists, astronomers, meteorologists and road specialists, and they prepared special maps on the environmental setting of the Libyan Sahara. As far as it is known, these special maps were never used by Axis troops (who fought in World War II against the Allies) for tactical purposes – although it cannot be ruled out that the maps provided general information on the proximity of the German Africa Corps, the Panzer Group Africa and of the Panzer Army Africa, respectively, and also of the retreating Army Group Africa.